2013
DOI: 10.1007/978-4-431-54270-4_28
|View full text |Cite
|
Sign up to set email alerts
|

Boson-Fermion Correspondence of Type B and Twisted Vertex Algebras

Abstract: The boson-fermion correspondence of type A is an isomorphism between two super vertex algebras (and so has singularities in the operator product expansions only at z = w). The boson-fermion correspondence of type B plays similarly important role in many areas, including representation theory, integrable systems, random matrix theory and random processes. But the vertex operators describing it have singularities in their operator product expansions at both z = w and z = −w, and thus need a more general notion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…This is possible by a "change of localization", and gives rise to new multilocal symmetries generated by the corresponding multilocal current and stress-energy tensor. The result gives a common underlying explanation of several remarkable recent results on the representation of the free Bose field in terms of free Fermi fields [1,2], and on the modular theory of the free Fermi algebra in disjoint intervals [7,15].…”
supporting
confidence: 60%
See 2 more Smart Citations
“…This is possible by a "change of localization", and gives rise to new multilocal symmetries generated by the corresponding multilocal current and stress-energy tensor. The result gives a common underlying explanation of several remarkable recent results on the representation of the free Bose field in terms of free Fermi fields [1,2], and on the modular theory of the free Fermi algebra in disjoint intervals [7,15].…”
supporting
confidence: 60%
“…The fact that the current (3.1) j(x) = i : ψ (1) (x)ψ (2) (x) : satisfies the CCR (3.2) is purely algebraic, and therefore independent of the representation. Taking ψ (1) in the Ramond representation and ψ (2) in the vacuum representation, the isomorphism (5.1) embeds the resulting current into the Ramond algebra π R CAR(S 1 ) . The result is (in the compact picture)…”
Section: The Ramond Casementioning
confidence: 99%
See 1 more Smart Citation
“…Then the answer to our "generating descendants" problem is: the fields a i (z) will generate a twisted vertex algebra. Twisted vertex algebras of general order N were defined in [Ang12] (of order 2 in [Ang13]) in order to answer the question: what are the boson-fermion correspondences of type B, C and D-A? These correspondences must be isomorphisms between some type of structures, and we wanted to understand those structures.…”
Section: Twisted Vertex Algebrasmentioning
confidence: 99%
“…The correspondence of type A is an isomorphism of super vertex algebras, but most boson-fermion correspondences cannot be described by the concept of a super vertex algebra due to the more general singularities in their operator product expansions. In order to describe the more general cases, including the correspondences of types B, C and D-A, in [Ang13a] and [Ang13b] we defined the concept of a twisted vertex algebra which generalizes super vertex algebra. By utilizing the bicharacter construction in [Ang13b] we showed that the correspondences of types B, C and D-A are isomorphisms of twisted vertex algebras.…”
Section: Introductionmentioning
confidence: 99%